Formulasi Sediaan Serum Wajah dari Ekstrak Sarang Burung Walet: Formulation of Facial Serum Preparations from Edible Bird's Nest Extract - Ina Annisa Rahmadina; Fajar Prasetya; Nur Masyitah Zamruddin (Proceeding of Mulawarman Pharmaceuticals Conferences, 2023)
The swallow's nest (Edible bird's nest) is included in the Apodidae family. Swallow's nest contains several proteins and amino acids, glutathione and antioxidants. Swallow's nest also contains EGF (Epideral grow factor) which functions to regulate cell growth and development. Facial serum is a preparation with a high concentration of active substances and low viscosity, which can deliver a thin film of active ingredients to the skin surface. The results of this study aim to examine the stability of facial serum formulations from edible bird's nest extract. The results of this research produced facial serum preparations. The results of the physical testing showed that the swallow's nest extract facial serum preparation looked stable without any sediment. Keywords: Edible bird's nest, facial serum, stability test Abstrak Sarang burung walet (Edible bird’s nest) termasuk dalam family Apodidae. Sarang burung walet mengandung beberapa protein dan asam amino, glutathione serta antioksidan. Sarang burung walet juga mengandung EGF (Epideral grow factor)yang berfungsi mengatur pertumbuhan dan perkembangan sel. Serum wajah merupakan sediaan dengan zat aktif konsentrasi tinggi dan viskositas yang rendah, yang dapat menghantarkan film tipis dari bahan aktif pada permukaan kulit. Hasil dari penelitian ini bertujuan untuk melihat stabilitas formulasi sediaan serum wajah dari ekstrak sarang burung walet (Edible bird’s nest). Hasil penelitian ini menghasilkan sediaan serum wajah. Hasil dari pengujian fisik terlihat sediaan serum wajah ekstrak sarang burung walet terlihat stabil tanpa ada endapan. Kata Kunci: Edible bird’s nest, serum wajah, Uji stabilitas